Answer:
I cant even see anything can you reupload your answer, please?
Step-by-step explanation:
Answer: OPTION C.
Step-by-step explanation:
1. To solve this problem you must apply the Pythagorean Theorem, which is shown below:
![a^{2}=b^{2}+c^{2}](https://tex.z-dn.net/?f=a%5E%7B2%7D%3Db%5E%7B2%7D%2Bc%5E%7B2%7D)
Where a is the hypotenuse, and b and c are the legs of the triangle.
2. When you solve for one of the legs and substitute values, you obtain that the result is:
![b=\sqrt{a^{2}-c^{2}}\\b=\sqrt{(24.8ft)^{2}-(8ft)^{2}}\\b=23.5ft](https://tex.z-dn.net/?f=b%3D%5Csqrt%7Ba%5E%7B2%7D-c%5E%7B2%7D%7D%5C%5Cb%3D%5Csqrt%7B%2824.8ft%29%5E%7B2%7D-%288ft%29%5E%7B2%7D%7D%5C%5Cb%3D23.5ft)
9x - 2y = 11 ... (i)
5x - 2y = 15 ... (ii)
Subtracting equation (ii) from (i) we get;
4x + 0 = -4
4x=-4 , x = -1
Replacing x = -1 in equation (i) we get;
9(-1) - 2y = 11
-9 - 2y = 11
-2y = 20
y = 20 ÷ -2 = -10
The solution to the system of equations is (-1,-10).
Answer:
i tried but i dont understand sorry
Step-by-step explanation: